The Role of Trading Halts in Monitoring a Specialist Market - Edelen, Roger; Gervais, Simon (Review of Financial Studies, 2003)
When a collection of specialists organize as an exchange, each can reap net private benefits at the expense of the exchange by quoting a privately optimal pricing schedule. Coordination makes all specialists and customers better off, but requires a system of monitoring and punishment that breaks down when information asymmetries between the exchange and a specialist are high. The specialist may then seek a temporary trading halt to alleviate unjustified punishment, or the exchange may halt trading to prevent the quoting of damaging privately optimal pricing schedules. We test this theory on a sample of NYSE halts. As predicted, we find a significant increase in estimated information asymmetry immediately preceding trading halts.